Molluscs of the “Real Orto Botanico di Napoli” - Duraccio, Sergio; Fasulo, Giuseppe; D’Anna, Gianni; Pingitore, Alberto; Soppelsa, Ottavio (BORNH Bulletin of Regional Natural History, 2021)
The results of two years of research on the molluscs present in the Botanical Garden of Naples are reported and compared with the sole similar study published in 1875 and with other reports in the literature, the last of which published in 1930 by Boettger. As a general result, a noticeable decrease in the number of species present in the site was recorded. However, some species not reported before have also been observed, and namely Vallonia costata (O.F. Müller, 1774), Orcula dolium (Draparnaud, 1801) and Planorbarius corneus (Linnaeus, 1758), all recorded for the first time in Campania, and in addition Carychium minimum O.F. Müller, 1774, which appears to be well settled in the studied enclave; for this latter species the only previous indication was found in the bibliography for Campania (Bellini 1898). Finally, some limacid slugs, previously found and recorded only by Boettger (1930), have been found.